The Impact of Foreign Ownership on Innovation Performance in Transition Economies, Using China as an Example - Gong, Lili (2016)
Foreign ownership refers to the complete or majority control of a business owned by foreign citizens or companies whose headquarters are in another country. This kind of ownership structure can provide companies in transition economies with various benefits. Foreign headquarters can supply domestic firms with more funds. Beyond mere financial contributions, foreign headquarters can also continuously transfer advanced knowledge and managerial know-how to local subsidiaries. Different types of talents may be allocated to these companies as well, which can be helpful to local economic development. Innovation has been a quite heated topic in many transition economies in recent years. Especially in China, where citizens always make money at a cost of their resources and the environment, now people have increasingly realized the importance of innovation. Much light has been shed on traditional factors that can have an impact on innovation, such as firm size, firm profitability and so on. Thus, the more recently discovered factor, foreign ownership, becomes the emphasis of this article. Although many scholars have investigated into the relationship between foreign ownership and firm-level innovation, the results have turned out to be inconsistent. Furthermore, most research on this topic is done based on data in developed countries, while not so much emphasis has been laid on transition economies. Nowadays, transition economies, such as China and India, have been constantly rising in importance. As a result, the author is going to dig deeper into the relationship between innovation and foreign ownership in transition economies, using China as an example. In this article, the author has gathered quantitative data from authorized websites such as CNINF, the only website which is designated by China Securities Regulatory Commission to disclose information about Chinese listed firms, and SIPO, which represents the State Intellectual Property Office of the People’s Republic of China. Negative binomial regression is used to discover the relationship between innovation performance and foreign ownership, and some significantly positive effects have been discovered.